Correlation of Receptor Occupancy of Metabotropic Glutamate Receptor Subtype 1 (mGluR1) in Mouse Brain With In vivo Activity of Allosteric mGluR1 Antagonists - Gentaroh Suzuki; Hiroko Kawagoe-Takaki; Takao Inoue; Toshifumi Kimura; Hirohiko Hikichi; Takashi Murai; Akio Satow; Mikiko Hata; Shunsuke Maehara; Satoru Ito; Hiroshi Kawamoto; Satoshi Ozaki; et al. (Elsevier, 2009)
Abstract.: The aim of this study was to clarify the relationship between receptor occupancy and In vivo pharmacological activity of mGluR1 antagonists. The tritiated mGluR1-selective allosteric antagonist [3H]FTIDC (4-[1-(2-fluoropyridin-3-yl)-5-methyl-1H-1,2,3-triazol-4-yl]-N-isopropyl-N-methyl-3,6-dihydropyridine-1(2H)-carboxamide) was identified as a radioligand having high affinity for mGluR1-expressing CHO cells (KD = 2.1 nM) and mouse cerebellum (KD = 3.7 nM). [3H]FTIDC bound to mGluR1 was displaced by structurally unrelated allosteric antagonists, suggesting there is a mutual binding pocket shared with different allosteric antagonists. The binding specificity of [3H]FTIDC for mGluR1 in brain sections was demonstrated by the lack of significant binding to brain sections prepared from mGluR1-knockout mice. Ex vivo receptor occupancy with [3H]FTIDC revealed that the receptor occupancy level by FTIDC correlated well with FTIDC dosage and plasma concentration. Intracerebroventricular administration of (S)-3,5-dihydroxyphenylglycine is known to elicit face washing behavior that is mainly mediated by mGluR1. Inhibition of this behavioral change by FTIDC correlated with the receptor occupancy level of mGluR1 in the brain. A linear relationship between the receptor occupancy and In vivo activity was also demonstrated using structurally diverse mGluR1 antagonists. The receptor occupancy assays could help provide guidelines for selecting appropriate doses of allosteric mGluR1 antagonist for examining the function of mGluR1 In vivo. Keywords:: metabotropic glutamate receptor, receptor occupancy, radioligand binding, allosteric antagonist, central nervous system